2018
DOI: 10.4236/ajps.2018.97113
|View full text |Cite
|
Sign up to set email alerts
|

Population Fluctuation and Vertical Distribution of the Soybean Looper (<i>Chrysodeixis includes</i>) in Soybean Culture

Abstract: The objective of this work was to study the population fluctuation and the vertical distribution of the Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) in the leaf canopy of soybeans. The experiments were conducted under field conditions in the experimental area of the Embrapa Agropecuária Oeste during the 2014/2015 harvest. Adult monitoring was performed using Delta-type traps, baited with the pest sexual pheromone. The eggs were collected in the soybean plants and the caterpillars monitored through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, due to the fact that it will be in constant movement it can result in more efficient chemical control of this species in non‐ Bt soybean fields. In Brazil, C. includens larvae were observed to prefer to position themselves predominantly in the lower and mid region of the soybean plants, 48 less exposed to insecticide, while the capacity of A. gemmatalis to move longer distances in the canopy may expose it more readily to treatment. Moreover, larval movement behavior and the difference in distance moved between the species emphasizes the importance of understanding on‐plant movement 49 , 50 and plant‐to‐plant movement of lepidopterans 51–53 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to the fact that it will be in constant movement it can result in more efficient chemical control of this species in non‐ Bt soybean fields. In Brazil, C. includens larvae were observed to prefer to position themselves predominantly in the lower and mid region of the soybean plants, 48 less exposed to insecticide, while the capacity of A. gemmatalis to move longer distances in the canopy may expose it more readily to treatment. Moreover, larval movement behavior and the difference in distance moved between the species emphasizes the importance of understanding on‐plant movement 49 , 50 and plant‐to‐plant movement of lepidopterans 51–53 .…”
Section: Discussionmentioning
confidence: 99%
“…These reports by Rattes and Jakoby (2020) differ from those observed in this study in that the number of stink bugs in the upper part of soybeans, especially for adults, which increased between 11 am and 2 pm, when the average day temperatures were highest although they migrated for the middle part of soybeans, after these times ( Figure 3 and Table 1). Zulin et al (2018), evaluating the behavior of small and large caterpillars of C. includens (Walker, 1858) (Lepidoptera, Noctuidae) in the three strata of soybean plants, observed a higher concentration of caterpillars in the upper stratum of the plant under conditions of milder ambient temperatures. From 10 am, these caterpillars started to move to the middle and lower parts of the soybean plants and later they went to the top of the plants, especially around 8 pm, thus presenting an opposite result from what we observed for E. heros, although this was another group of soybean pests.…”
Section: Discussionmentioning
confidence: 99%
“…Rattes & Jakoby (2020) reported that adult's soybean phytophagous stink bugs have a habit of moving to the upper canopy of plants in the morning while at the hottest periods of the day they move to the middle third. Zulin et al (2018) also found that caterpillars of Chrysodeixis includens (Walker, 1858) (Lepidoptera: Noctuidae) were more exposed in the upper strata of soybean plants during the coolest times of the day, such as in the early hours of the morning and at night. Similar work was also carried out by Waite (1980) on soybean for the green stink bug, Nezara viridula (Linnaeus, 1758) (Hemiptera, Pentatomidae).…”
Section: Introductionmentioning
confidence: 97%
“…While, in the USA, C. includens is migratory in some parts of the territory due to extreme low temperatures (Herzog 1980), milder weather conditions and the yearround presence of crops theoretically favor the occurrence and abundance of polyphagous insects as this one in the Brazilian Cerrado. Nevertheless, its presence is hardly detected in most months and elevated abundances are restricted to a little part of the rainy season and practically synchronic to soybean availability (Santos et al 2017;Zulin et al 2018). Favorable temperatures present in these regions, and the availability of a rich source of nutrition may be associated to the presence of the insect during a specific time of the year.…”
Section: Introductionmentioning
confidence: 99%